2007
DOI: 10.1080/07373930701438428
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Two Models of Convective Drying of Shrinking Materials Using Apple Tissue as an Example

Abstract: Modeling of drying of capillary-porous materials is a mathematically complex problem. It takes into consideration simultaneous heat and mass transfer inside the material with physicochemical properties changing during the drying process. Modeling of the process mentioned above consists of describing the heat and mass transfer balances by means of differential equations. Moisture diffusion coefficient as a function of moisture content and temperature of the material is a crucial parameter that controls the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…Complex optimization procedures need to be conducted subsequently to represent the dependence of diffusivity on moisture content and/or temperature (Azzouz et al, 2002;Pakowski and Adamski, 2007;Mariani et al, 2008;Vaquiro et al, 2009;Ramos et al, 2010;Silva et al, 2010;Ruiz-Lopez et al, 2011). Pakowski and Adamski (2007) and Ruiz-Lopez et al (2011) showed that various mathematical expressions of diffusivity need to be attempted to yield the most appropriate diffusivity function. It can be observed that the experimental data is required by both diffusion approach and the REA in order to generate the parameters but the REA requires more efficient procedures than the diffusion based approach to generate the drying parameters.…”
Section: Brief Review Of the Reamentioning
confidence: 99%
See 1 more Smart Citation
“…Complex optimization procedures need to be conducted subsequently to represent the dependence of diffusivity on moisture content and/or temperature (Azzouz et al, 2002;Pakowski and Adamski, 2007;Mariani et al, 2008;Vaquiro et al, 2009;Ramos et al, 2010;Silva et al, 2010;Ruiz-Lopez et al, 2011). Pakowski and Adamski (2007) and Ruiz-Lopez et al (2011) showed that various mathematical expressions of diffusivity need to be attempted to yield the most appropriate diffusivity function. It can be observed that the experimental data is required by both diffusion approach and the REA in order to generate the parameters but the REA requires more efficient procedures than the diffusion based approach to generate the drying parameters.…”
Section: Brief Review Of the Reamentioning
confidence: 99%
“…The models may not be practical for applications in industries where quick and accurate decisionmaking is necessary. In particular, the diffusivity needs to be estimated as a function of temperature and water content (Azzouz et al, 2002;Ruiz-Lopez and Garcia-Alvarado, 2007;Pakowski and Adamski, 2007;Mariani et al, 2008;Vaquiro et al, 2009;Ramos et al, 2010;Silva et al, 2010). In addition, Crank's effective liquid-diffusion based model implemented by several researchers (Steffe and Singh, 1982;Cihan and Ece, 2001;Ramesh, 2003;Iguaz et al, 2003) offers simplicity of mathematical modeling and computation so that diffusivity can be simply determined (but rather roughly) by taking slope of reduced moisture content versus time.…”
Section: Introductionmentioning
confidence: 99%
“…(1), the diffusion of moisture in cylindrical-shaped pasta can be expressed as (Pakowski & Adamski, 2006) …”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…Osmotic dehydration (OD) as a pretreatment process before proper drying enables moisture removal from vegetables and fruits up to 50%. Besides, the application of osmotic pretreatment considerably reduces chemical, physical and biological adverse changes which occur during long lasting convective drying, called hot air drying (Kowalska and Lenart, 2001;Pakowski and Adamski, 2007;Piasecka et al, 2012;Witrowa-Rajchert and Rząca, 2009). …”
Section: Introductionmentioning
confidence: 99%